Common symptoms, rare diagnosis – paediatric visceral leishmaniasis in a non-endemic region - Warchoł, Aleksandra; Szymońska, Izabela; Kania, Urszula; Kwinta, Przemko; Paul, Małgorzata (Pediatria Polska - Polish Journal of Paediatrics, 2024)
We hereby present a case of a 5-year-old Polish girl suffering from visceral leishmaniasis (VL) – a worldwide-spread parasitic disease. Due to persistent fever and hepatosplenomegaly, the patient was initially diagnosed with juvenile rheumatoid arthritis. Ineffective treatment of the disease led to repeated inspection of bone marrow, which was analysed in 3 laboratories in Poland, with only one correctly recognising the parasite infiltration. Detailed history revealed traveling to regions endemic for Leishmania spp. in the Mediterranean Sea Region and South America, visited between 3 months – 3.5 years before the onset of the disease. The final diagnosis of the disease was based on bone marrow aspiration and a polymerase chain reaction blood test. Pentavalent antimonial therapy was successfully administered. The case report presents the difficulties in diagnosing VL in a non-endemic country and provides a review of the current literature on the management of VL in children.